Diversity of Waterbirds in the Wetland of Pangpang Bay Essential Ecosystem Area, Banyuwangi, Indonesia - Fahrani, Elyn; Susintowati, Susintowati; Nugrahani, Magdalena Putri; Sungkono, Sungkono; Prasetyo, Yusuf Eko (Bioeksperimen: Jurnal Penelitian Biologi, 2024)
The Essential Ecosystem Area (KEE) of Teluk Pangpang, Banyuwangi is a wetland that is passed by the East Asia Australia Flyway (EAAF) bird migration route. This study aims to study the diversity, and abundance of waterfowl species, and the relationship between the existence of waterfowl species and environmental factors in each type of wetland habitat. This study was conducted in October 2023-January 2024 using the "Concentration Count" method on each type of wetland habitat, observations were made for 2-3 hours concerning the tidal schedule of seawater. Based on observations, 34 species of waterbirds were found in all wetland habitats with a total number of 7468 individuals. The mud stretch of Muncar Beach has the highest species diversity with a total of 32 species of waterbirds, while the Kili-Kili mangrove habitat has the lowest level of species diversity with a total of 5 species of waterbirds. There have been 22 species of migratory waterbirds, 8 species of resident waterbirds, and 4 species of migratory resident waterbirds. Based on IUCN status, 5 species were found to be near threatened (NT), and 3 species were endangered (EN). The abundance of the highest waterbird species, namely Bulbulus ibis,  is 3742 individuals that dominate the mangrove habitat. The value of the index of waterfowl species diversity in each type of wetland habitat is included in the medium category (H'=1,895 – 2,594.), except for the low category of mangrove habitat (H'=0.719). The results of the PCA show that the existence of waterfowl is influenced by habitat conditions and environmental parameters (temperature, air humidity, light intensity, salinity).